Evaluation of the Ki-67 and MCM3 Expression in Cytologic Smear of Oral Squamous Cell Carcinoma - Fahimeh Rezazadeh; Rahele Ebrahimi; Azadeh Andisheh-Tadbir; Mohammad Javad Ashraf; Bijan Khademi (Shiraz University of Medical Sciences, 2017)
Statement of the Problem: Squamous cell carcinoma (SCC) is the most frequent oral cancer whose 5-year survival rate is 80% for early-detected lesions and nearly 30-50% for advanced lesions. Early detection of oral cancers and precancerous lesions can improve the patient's survival and decrease the morbidity. Purpose: This study aimed to evaluate and compare the Ki-67 and MCM3 expression in cytologic smear of oral SCC (OSCC). Materials and Method: We examined 48 oral brush biopsies including 28 OSCC and 20 healthy non-smoking samples. Immunocytochemistry staining was performed for Ki-67 and MCM3 by using an EnVision-labeled peroxidase system, and labeling index (LI) was calculated. Results: Out of 28 OSCC cases, 27(96.4%) cases contained MCM3 positive cells and 22(78%) cases contained Ki-67 positive cells. All normal mucosa were Ki-67 and MCM3 negative. MCM3 and Ki-67 LI were significantly higher in OSCC than normal mucosa (p< 0.001). MCM3 LI was significantly higher than Ki-67 LI in OSCC group (p< 0.001). Conclusion: Immunocytologic evaluation of Ki-67 and MCM3 can be used for early detection of OSCC. Furthermore, MCM3 may be a more sensitive cytologic biomarker than Ki-67 in SCC patients.